Grain Boundary Engineering Enabled High‐Performance Garnet‐Type Electrolyte for Lithium Dendrite Free Lithium Metal Batteries. Issue 9 (19th July 2022) - Zheng, Chujun; Lu, Yan; Su, Jianmeng; Song, Zhen; Xiu, Tongping; Jin, Jun; Badding, Michael E.; Wen, Zhaoyin
Abstract: Solid‐state lithium metal batteries (SSLMBs) are attracting increasing attentions as one of the promising next‐generation technologies due to their high‐safety and high‐energy density. Their practical application, however, is hindered by lithium dendrite growth and propagation in solid‐state electrolytes (SSEs). Herein, an in situ grain boundary modification strategy relying on the reaction between Li2 TiO3 (LTO) and Ta‐substituted garnet‐type electrolyte (LLZT) is developed, which forms LaTiO3 along with lesser amounts of LTO/Li2 ZrO3 at the grain boundaries (GBs). The second phases of LTO/Li2 ZrO3 inhibit abnormal grain growth. The presence of LaTiO3 at the GBs reduces electronic conductivity and improves mechanical strength, which can hinder dendrite formation and block lithium dendrite penetration through the LLZT. Moreover, the adjacent grains by LaTiO3 build a continuous Li + transport path, providing a homogeneous Li + flux throughout the whole LLZT‐4LTO. As a result, symmetric cells of Li | LLZT‐4LTO | Li shows a high critical current density of 1.8 mA cm −2 and a long cycling stability up to 2000 h at 0.3 mA cm −2 . Moreover, the high‐voltage full cells demonstrate remarkable cycling stability and rate performance. It is believed that this novel grain boundary modification strategy can shed light on the constructing of high‐performance SSEs for practical SSLMBs. Abstract : The grain boundary engineering gives the garnet electrolyte superior lithium dendrite suppression capability.